Probabilistic Surface Heat Flow Estimates Assimilating Paleoclimate History: New Implications for the Thermochemical Structure of Ireland. Issue 12 (5th December 2018) - Mather, Ben; Farrell, Thomas; Fullea, Javier
Abstract: Regions where surface temperature has increased since past glaciation events, such as Ireland, underestimate the heat output of the Earth unless paleoclimate corrections are applied. We apply probabilistic techniques to quantify the uncertainty of 22 paleoclimate‐corrected heat flow estimates in Ireland, which assimilate multiple surface temperature histories associated with 130 ka of glacial oscillation in the British Isles. Heat flow values increase by ∼15 mW/m 2 after a paleoclimate correction and provide new insights into the thermochemical structure of the lithosphere. The heat flow regime is broadly delineated by the Iapetus Suture Zone that separates Laurentian to the north and Avalonian terranes to the south (mean surface heat flow of 73 ± 14 and 65 ± 14 mW/m 2, respectively). The degree to which heat‐producing elements are partitioned into the uppermost crust is described by the differentiation index of a heat flow province. From Bayesian inversion, we determine that radiogenic elements are substantially more differentiated in the uppermost crust of Laurentia ( D I =2.8 ± 1.4) than Avalonia ( D I =1.5 ± 1.3), despite a moderately enriched lower crust (0.8 ± 0.3 μW/m 3 ). This is facilitated by a thin yet highly radiogenic layer in the uppermost crust of Laurentia (3.9 ± 1.8 μW/m 3 ). Extrapolating these results across the British Isles and Newfoundland suggests that heat‐producing elements have been more successfully reworked into the upper crust to the north of the Iapetus Suture Zone during continental accretion between Laurentia and Avalonia. Key Points: Average surface heat flow has increased by 20% after probabilistic paleoclimate corrections are applied Laurentian and Avalonian heat flow provinces are identified, delineated by the Iapetus Suture Zone A higher degree of radiogenic differentiation is recognized in the upper crust of Laurentia, compared to that of Avalonia